2016
DOI: 10.3390/su8121345
|View full text |Cite
|
Sign up to set email alerts
|

Multi-Regional Input-Output (MRIO) Study of the Provincial Ecological Footprints and Domestic Embodied Footprints Traded among China’s 30 Provinces

Abstract: Rapid development in China has led to imbalances and inequities of ecological resources among the provinces and regions. In this study, an environmentally extended multi-regional input-output (MRIO) model was used to analyze the imbalances, inequities and pressures of the ecological footprints (EF) of China's 30 provinces in 2007. In addition, by decomposing the total product consumption coefficients, we calculated the net embodied EF of the flows among the provinces by the total amount, land type and sector. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 31 publications
(17 reference statements)
1
5
0
Order By: Relevance
“…On spatial distribution, it is consistent with the results of Wu et al [40]. On temporal variation, it is also in line with the results of Li et al [21] who founded an increasing trend from 1990 to 2010 in Shanxi, Gansu, Ningxia and Xinjiang, and of Yue et al [41] who showed a steadily growth in Gansu from 1995 to 2003.…”
Section: Discussionsupporting
confidence: 82%
“…On spatial distribution, it is consistent with the results of Wu et al [40]. On temporal variation, it is also in line with the results of Li et al [21] who founded an increasing trend from 1990 to 2010 in Shanxi, Gansu, Ningxia and Xinjiang, and of Yue et al [41] who showed a steadily growth in Gansu from 1995 to 2003.…”
Section: Discussionsupporting
confidence: 82%
“…where I is the identity matrix, and L is called Leontief inverse matrix (Wu and Liu 2016). Supposing there is a row vector D, each of its elements, [d r i ], represents the direct carbon emission intensity of the sector i in region r, that is, the production-based emissions of the sector i in region r divided by the total output of this sector.…”
Section: Consumption-based Emission Accounting Based On the Multi-reg...mentioning
confidence: 99%
“…Zhang et al, measure the virtual energy trade situation between various regions of China by using MRIO [41]. Decun and Jinping analyzed the energy footprint of various provinces in China in 2007 [42]. Chen et al tracked the use of freshwater resources in global supply chains [43].…”
Section: Literature Reviewmentioning
confidence: 99%